Bio-priming of banana tissue culture plantlets with endophytic Bacillus velezensis EB1 to improve Fusarium wilt resistance - Xiang, Dandan; Yang, Xiaofang; Liu, Bojing; Chu, Yuanqi; Liu, Siwen; Li, Chunyu (Frontiers in Microbiology, 2023)
Tissue culture techniques have been routinely used for banana propagation and offered rapid production of planting materials with favorable genotypes and free of pathogenic microorganisms in banana industry. Meanwhile, extensive scientific work suggests that micropropagated plantlets are more susceptible to Fusarium oxysporum f. sp. cubense (Foc), the deadly strain that causes Fusarium wilt of banana than conventional planting material due to the loss of indigenous endophytes. In this study, an endophytic bacterium Bacillus velezensis EB1 was isolated and characterized. EB1 shows remarkable in vitro antagonistic activity against Foc with an inhibition rate of 75.43% and induces significant morphological and ultrastructural changes alterations in the hyphae of Foc. Colony-forming unit (c.f.u.) counting and scanning electron microscopy (SEM) revealed that EB1 could colonize both the surface and inner tissues of banana tissue culture plantlets. Banana tissue culture plantlets of late rooting stage bioprimed with EB1 could efficiently ward off the invasive of Foc. The bio-priming effect could maintain in the acclimatized banana plants and significantly decrease the disease severity of Fusarium wilt and induce strong disease resistance by manipulating plant defense signaling pathways in pot experiment. Our results provide the adaptability and potential of native endophyte EB1 in protecting plants from pathogens and infer that banana tissue culture plantlets bio-priming with endophytic microbiota could be a promising biological solution in the fight against Fusarium wilt of banana.